Systematic review of self‐management interventions for older adults with cancer. Issue 7 (16th March 2021) - Haase, Kristen R.; Sattar, Schroder; Hall, Steven; McLean, Bianca; Wills, Aria; Gray, Mikaela; Kenis, Cindy; Donison, Valentina; Howell, Doris; Puts, Martine
Abstract: Aim: The purpose of this systematic review was to determine the effectiveness of self‐management interventions for older adults with cancer and to determine the effective components of said interventions. Methods: We conducted a systematic review of self‐management interventions for older adults (65+) with cancer guided by the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis statement. We conducted an exhaustive search of the following databases: Ageline, AMED, ASSIA, CINAHL, Cochrane, Embase, Medline, PsychINFO, and Sociological Abstracts. We assessed for quality using the Cochrane Risk of Bias tool and Down & Black for quasi‐experimental studies, with data synthesized in a narrative and tabular format. Results: Sixteen thousand nine hundred and eight‐five titles and abstracts were screened, subsequently 452 full‐text papers were reviewed by two independent reviewers, of which 13 full‐text papers were included in the final review. All self‐management interventions included in this review measured Quality of Life; other outcomes included mood, self‐care activity, supportive care needs, self‐advocacy, pain intensity, and analgesic intake; only one intervention measured frailty. Effective interventions were delivered by a multidisciplinary teams ( n  = 4), nurses ( n  = 3), and mental health professionals ( n  = 1). Self‐management core skills most commonly targeted included: problem solving; behavioural self‐monitoring and tailoring; and settings goals and action planning. Conclusions: Global calls to action argue for increased emphasize on self‐management but presently, few interventions exist that explicitly target the self‐management needs of older adults with cancer. Future work should focus on explicit pathways to support older adults and their caregivers to prepare for and engage in cancer self‐management processes and behaviours.